Infaunalization and resource partitioning during the Mesozoic marine revolution - Buatois, Luis Alberto (2022)
Infaunalization has been regarded as representing a response to increased predation pressures and is therefore central to the Mesozoic marine revolution, which gives pre-eminence to the role that enemy-directed evolution has played as a driving force of biotic change. Our ichnologic compilation from 39 Middle Triassic to Late Jurassic shallow-marine siliciclastic units allows us to evaluate the vertical partitioning of the infaunal ecospace through the application of the ichnoguild concept. This study shows that infaunal communities experienced a marked increase in ecospace utilization during the Early Jurassic, reaching a plateau during the rest of the Jurassic. This trend is expressed by an increase in the maximum number of ichnoguilds per community and per tier and in the number of ichnotaxa per ichnoguild. This pattern shows important partitioning of the infaunal ecospace into a series of tiers and that several organisms were able to exploit the same resources available at discrete sediment zones below the sea bottom. The increase in the maximum number of ichnoguilds per community and per tier suggests that niche partitioning was a key factor in a more efficient use of the infaunal ecospace and in driving alpha diversity. However, the increase in the number of ichnotaxa per ichnoguild indicates that ichnoguilds were packed with organisms exploiting similar resources, arguing against the role of competitive exclusion in structuring communities. Because several episodes of predation increase took place during the Mesozoic, an unequivocal link between predation pressures and infaunalization cannot be demonstrated empirically.